RETRACTED: Fibrous Dysplasia of the Thyroid Cartilage – A Case Study and Review of the Literature - Pang, Aaron (Journal of Otolaryngology Advances, 2015)
This article has been retracted on 25 March 2016. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2379-8572.joa-25-5867) Fibrous dysplasia is a rare disorder of bone that is uncommon in the head and neck region. Herein, we present a rare case of polyostotic fibrous dysplasia involving the right temporal bone and thyroid cartilage in a 19-year-old male. This unique location necessitates close surveillance due to the proximity to the airway and the potential for malignant degeneration.
Keywords: Fibrous Dysplasia; Thyroid Cartilage; Polyostotic Fibrous Dysplasia; Temporal Bone; Head and Neck